The novel undulated parabolic trough receiver: performance enhancement, reduction in the size and cost of the collector fields - Demagh, Yassine; KABAR,Yassine; BITAM, El-Wardi (ISES Solar World Conference 2017 and the IEA SHC Solar Heating and Cooling Conference for Buildings and Industry, 2017)
One of the main options to drive the cost of parabolic trough collectors (PTCs) technology down is to reduce the size of the solar field. This work proposes a novel receiver longitudinally undulated as a replacement for the conventional straight tube and investigates the effects on the size of absorbers, PTC modules and entire solar field. For this purpose, the developed method based on the similitude analysis should provide tools for drawing a comparison between the various designs of the absorber and should give useful measures of the scenario of their commissioning. Undulated absorber in service and without added supplementary mechanical components; the size of a solar collector field should reduce about ~29.5% consequence of the reduced size of the solar collector module and the absorber. The increase of the pressure drops through the novel absorber pipe should be re-balanced by the reduction in its size.

The novel undulated parabolic trough receiver: performance enhancement, reduction in the size and cost of the collector fields - Demagh, Yassine; KABAR,Yassine; BITAM, El-Wardi (ISES Solar World Conference 2017 and the IEA SHC Solar Heating and Cooling Conference for Buildings and Industry, 2017)
One of the main options to drive the cost of parabolic trough collectors (PTCs) technology down is to reduce the size of the solar field. This work proposes a novel receiver longitudinally undulated as a replacement for the conventional straight tube and investigates the effects on the size of absorbers, PTC modules and entire solar field. For this purpose, the developed method based on the similitude analysis should provide tools for drawing a comparison between the various designs of the absorber and should give useful measures of the scenario of their commissioning. Undulated absorber in service and without added supplementary mechanical components; the size of a solar collector field should reduce about ~29.5% consequence of the reduced size of the solar collector module and the absorber. The increase of the pressure drops through the novel absorber pipe should be re-balanced by the reduction in its size